Biotic and geochemical response to anoxic events: The Aptian pelagic succession of the Gargano promontory (Southern Italy) - LUCIANI, Valeria; COBIANCHI M.; JENKYNS H. (Geological Magazine, 2001)
Microfossil distribution patterns and high-resolution d13C and d18O curves, calibrated against planktonic foraminiferal and calcareous nannofossil data, are provided for the Aptian pelagic Coppitella section of the Gargano Promontory (southern Italy). The succession consists of cyclically arranged couplets of bioturbated grey marlstones and off-white marly limestones, referable to the Marne a Fucoidi. In the lower portion of the section, two thin black shales were recognized. The highresolution d13C curve presented here correlates with those of other Alpine–Tethyan sections, albeit with lower absolute values. The onset of deposition of organic-rich sediments falls at the top of the interval of unchanging carbon-isotope values, whereas the upper black shale is documented from the interval of the main Aptian positive d13C excursion. According to our biostratigraphic data, the deposition of organic matter in the Gargano Promontory persisted through Early/Late Aptian boundary time. Using a chemostratigraphic definition, only the lower black shale is referred to the Selli Level. As far as the biotic response is concerned, the onset of the ‘nannoconid crisis’ is recorded considerably below the lower black shale, whereas the ‘Globigerinelloides eclipse’ is recorded below and within the upper black shale. The distribution of meso-eutrophic indices (Zygodiscus spp., radiolaria) vs. moderate-fertility indices (Rhagodiscus asper and Lithraphidites carniolensis) testifies to a modest increase of surfacewater fertility only throughout the stratigraphically higher black shale. The occurrence of a benthic foraminiferal fauna, albeit impoverished, in both the basal and upper black horizons clearly documents dysaerobic rather than completely anoxic conditions on the sea floor. Relative sea-level rise at the time of the Selli Event in the Gargano Promontory is documented by drowning and foundering of the Apulia platform margin, situated adjacent to the basin in which the Marne a Fucoidi accumulated.